A vezetői döntés értelmezése, a döntéshozatal szakaszai és támogatása - Hampel, György (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The decision plays an important role among manager activities. Sometimes it is mentioned independently besides other activities, sometimes it appears as part of other managerial functions. Decisions can be examined from several aspects: goodness, utility, expediency, rationality etc. Making a decision means choosing between at least two alternatives. The process is affected by several (logical and psychological) factors and it consists of some constantly recurring steps which cannot be easily separated in practice. It is vital for the modern enterprise leadership to make prompt and successful decisions and to do that, decision support (information) systems are needed. However, mangers should keep in mind that these systems are not to make decisions - hardware and software cannot take on responsibility - , their job is to help to make decisions.